On the fiber-optic chlorine sensor with enhanced sensitivity based on the study of evanescent field absorption spectroscopy - CHOUDHURY, P; YOSHINO, T (2004)
The paper deals with a fiber optic evanescent field absorption sensor that can be used for the detection of chlorine content in drinking water. The technique is based on the absorption of evanescent fields through the development of color owing to the reaction of an organic compound diethyl phenylene diamine with chlorine, which is already present in water. In the experiment, a U-shaped optical sensor probe is used because the sensitivity of the system improves due to the higher penetration depth achieved in this case. The improvement in sensitivity (in the case of U-shaped probed) is also shown experimentally.